A Guide to Meal Replacements - Lauren Headrick; Linda B. Bobroff (EDIS)
Many older Americans have problems eating enough to get the calories and nutrients needed for good health. Multiple factors such as disease, money, physical conditions, and access to food and food preparation areas can affect your nutritional status. Consuming meal replacements is one way to offset the effects of these factors. This 3-page fact sheet will help you decide if meal replacements are right for you. Written by Lauren Headrick and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, March 2012.